Building Purchase Intentions Through Source Credibility: The Mediating Role of Customer Attitude on TikTok Live Shopping in Padang City - Muhamad Haikal; Wiry Utami; Irda Irda (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aimed to examine the influence of source credibility on purchase intention mediated by customer attitude on TikTok live shopping in Padang City. The sample in this study consisted of 111 respondents with purposive sampling using questionnaire. Data were analyzed using Smart PLS version 3.0 with the following results: source credibility has a positive and significant effect on purchase intention. Then, source credibility has a positive and significant effect on customer attitude. Intervening variable testing shows that customer attitude variables can influence the indirect effect between source credibility on purchase intention.